Factors that Influence Cash Holding on Property and Real Estate Companies - Khairunnizam, Khairunnizam (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2022)
The purpose of this study is to examine the effect of leverage, firm size, net working capital, growth opportunities, dividend payout towards cash holdings. This type of research is quantitative. The population in this study were property and real estate companies that were listed in Indonesia stock exchange 2018-2020 period amounted to 62 companies. While the sample of this research is 12 companies with 36 observation data. The sampling method in this research is purposive sampling. The data used were secondary data. The data collection of this research is documentary. Test data analysis using multiple linear regression method which is processed using SPSS version 23 program. The result of this study is that leverage, firm size, net working capital, dividend payout affect cash holdings, while growth opportunities do not affect cash holdings..